2017
DOI: 10.18316/rca.v11i3.3371
|View full text |Cite
|
Sign up to set email alerts
|

TWO LEUCISM CASES IN Turdus rufiventris Vieillot, 1818 (BIRDS, TURDIDAE), IN SOUTHERN BRAZIL

Abstract: Dois casos de leucismo em Turdus rufiventris (Aves, Turdidae), no sul do Brasil. A presente comunicação reporta dois casos de leucismo em Turdus rufiventris, no Sul do Brasil. Um espécime mutante foi registrado em perímetro urbano, no município de Santa Cruz do Sul, Rio Grande do Sul, Brasil. O indivíduo apresentava rêmiges secundárias totalmente brancas na asa esquerda, e coloração normal no restante do corpo. O segundo espécime foi registrado num fragmento florestal, em área rural no município de Santa Maria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…is characterizes a case of Progressive Greying mutation, according to van Grouw (2013) and Hume and van Grow (2014). Many cases of chromatic mutation in birds in Brazil have been related in literature (e.g., Piacentini, 2001;Corrêa et al, 2013;De-Carvalho et al, 2015;Corrêa et al, 2017a, b;Lopes et al, 2017;Mohr et al, 2017;Petry et al, 2017), being leucism reported more frequently (Corrêa et al, 2017b;Mohr et al, 2017). We believe these records reported here in this study are the rst mutation described for R. americana and R.…”
Section: Occurrence Descriptionsupporting
confidence: 66%
See 1 more Smart Citation
“…is characterizes a case of Progressive Greying mutation, according to van Grouw (2013) and Hume and van Grow (2014). Many cases of chromatic mutation in birds in Brazil have been related in literature (e.g., Piacentini, 2001;Corrêa et al, 2013;De-Carvalho et al, 2015;Corrêa et al, 2017a, b;Lopes et al, 2017;Mohr et al, 2017;Petry et al, 2017), being leucism reported more frequently (Corrêa et al, 2017b;Mohr et al, 2017). We believe these records reported here in this study are the rst mutation described for R. americana and R.…”
Section: Occurrence Descriptionsupporting
confidence: 66%
“…Cases of chromatic mutations in birds, despite frequency it appears, must be published, once it is possible the occurrence of many reported cases in wild life still don't registered yet, considering some researchers and/or photographers don't publish in peer reviewed journals (Corrêa et al, 2017a;Petry et al, 2017), what can result in a underestimation of such events (De-Carvalho et al, 2015;Sainz-Borgo et al, 2016). ese mutations can be associated to many natural or anthropic factors (e.g., Bensch et al, 2000;van Grouw, 2006), documentation and description of such cases become crucial, evidencing feathering variation and a ected species (Corrêa et al, 2013;Mohr et al, 2017).…”
Section: Occurrence Descriptionmentioning
confidence: 99%
“…By checking descriptions in van Grouw (2006;2013;, we identi ed a case of total leucism for T. ru ventris, and a case of progressive mutation for M. saturninus (Figure 1). In Argentina, Urcula (2011) mentions a specimen of M. saturninus with leucism, and some cases of aberrant coloring in T. ru ventris, speci cally albinism and leucism, were reported in the Brazilian territory by Veiga and Pardo (1990), Piacentini (2001), Júnior et al (2008, Santos et al (2008), Júnior and Corrêa 2017, and Mohr et al (2017).  ese events are not uncommon in nature (van Grouw et al, 2011), and in the State of Rio Grande do Sul, several cases of birds with aberrant coloring have recently been reported, for instance: Corrêa et al (2012), Düpont et al (2014), Corrêa et al (2017), Júnior and Corrêa (2017), Mohr et al (2017) and Vieira et al (2018).…”
Section: Occurrence Descriptionmentioning
confidence: 97%